Measurement Of The Level Of Acceptability Of UNPAZ Academics To The Resolution Of The Government Of Timor Leste Regarding The Suspension Of Doctoral Study Programs - Galaciano, Antoninho Benjamin Marcos M.G. Do Rego; Sutoyo; Zainuddin, Ahmad; Suminar, Lintang; Soleha, Siti Nur (Abadi Institute, 2025)
The Government of Timor-Leste’s decision to suspend doctoral programs has elicited varied responses from academics concerning their perception, participation, and acceptance of the policy. This study aims to analyze the influence of academics’ perception and participation on their acceptance of the doctoral program closure policy. Employing a quantitative approach, the research involved 257 academics from UNPAZ, selected through purposive and convenience sampling. Data were analyzed using PLS-SEM to test direct and mediating effects among variables, complemented by non-parametric analyses (Kruskal-Wallis, Mann-Whitney, and logistic regression) to examine differences across demographic groups. The findings reveal that academics’ perception and participation simultaneously exert a significant effect on policy acceptability. Academics with higher education and greater academic engagement, such as lecturers and postgraduate students, demonstrated lower levels of acceptability compared to undergraduate students and administrative staff. Non-parametric results further confirmed significant differences based on age, educational level, and academic status. Overall, academics’ acceptability of the doctoral program closure policy is relatively low and influenced by both perception and active participation, with higher educational attainment associated with more critical attitudes toward the policy. Therefore, it is recommended that the Government of Timor-Leste improve transparent communication and participatory mechanisms to foster positive perceptions and stronger policy support, while encouraging academics to take a more active role in the policy-making process.